2000
DOI: 10.1021/om000190m
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio MO Study of Silver Ion Complexation in [2.2.2]Cyclophane π-Prismands

Abstract: Ab initio Hartree-Fock and DFT MO calculations have been used to study the conformations of [2.2.2]cyclophane π-prismands and the formation of π-complexes with silver ion and [2.2.2]cyclophanes. The lowest energy cyclophane conformations have been calculated up to the HF/6-31+G* level of theory. The silver π-complexes of the lowest energy conformations have been calculated with HF/3-21G* and B3LYP/3-21G* levels of theory. The nature of bonding in silver ion π-complexes has been studied with natural bond orbita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 18 publications
4
10
0
Order By: Relevance
“…Some selected bond and torsion angles of the most stable conformations of the B3LYP-optimised cyclophanes are shown with the experimental values obtained from X-ray analysis in Table 2. These calculated bond parameters agree well with previously reported values in similar cyclophanes, [16,17] and are also in very good agreement with experimental Xray values. Based on the very good agreement between the calculated structure and the X-ray structure for 21, the calculated structure presented here for [2.2.0] m,m,m-cyclophane (20) (Figure 9) can be accepted as a good model of its structure, [a] Numbering according to Figure 8.…”
Section: Molecular Orbital Calculationssupporting
confidence: 91%
See 1 more Smart Citation
“…Some selected bond and torsion angles of the most stable conformations of the B3LYP-optimised cyclophanes are shown with the experimental values obtained from X-ray analysis in Table 2. These calculated bond parameters agree well with previously reported values in similar cyclophanes, [16,17] and are also in very good agreement with experimental Xray values. Based on the very good agreement between the calculated structure and the X-ray structure for 21, the calculated structure presented here for [2.2.0] m,m,m-cyclophane (20) (Figure 9) can be accepted as a good model of its structure, [a] Numbering according to Figure 8.…”
Section: Molecular Orbital Calculationssupporting
confidence: 91%
“…The structure of the [2.2.2]p,p,p-cyclophane (1) ionophore seems to be particularly favourable for Ag ϩ -π interactions, resulting in ISEs with the best Ag ϩ selectivity among the cyclophanes studied. [14,15] The nature of the bonding in π-prismands and the conformations of [ [16,17] Following the syntheses and testing of [2.2.1]cyclophanes, we were extremely interested to study even smaller and more strained hydrocarbon cyclophanes, i.e. [2.2.0]m,m,mcyclophane (20) [18] and [2.2.0]p,m,m-cyclophane (21) [19] to see if even more rigid and distorted cyclophanes than [2.2.1]cyclophanes can act as π-prismands.…”
Section: Introductionmentioning
confidence: 99%
“…We performed computations in order to gain information about the structure of 4 ⋅Ag + and confirm the results obtained by NMR spectroscopy. It has been shown that HF/3‐21G* and B3LYP/3‐21G* calculations are able to reproduce the geometries of cyclophane⋅Ag + complexes reasonably well, with omission of the triflate anion in the computation model 39. The calculated structures are in agreement with those obtained by X‐ray structural analysis.…”
Section: Resultssupporting
confidence: 64%
“…In contrast, Ag + and Pd have an accessible 4d 10 shell. The large energetic differences Δ E of the planar versus the prismatic form, as well as the short MC separation, suggest that d‐orbital bonding contributions are most important for the Pd complex but are, to a lesser extent, also important for the Ag complex 37. A full analysis of the nature of this bonding is in progress 35…”
Section: Comparison Of Experimental and Dft‐calculated Properties Of mentioning
confidence: 99%